PENGARUH KOMITMEN, MOTIVASI KERJ DAN PROFESIONALISME PERAWAT TERHADAP MUTU PELAYANAN DI RUMAH SAKIT UNDATA PALU - Saat, Saat (Katalogis, 2015)
This research aims to find aur and analyze the effect of commitmen, working motivation, and professionalism toward service quality either simultaneously or partially. The respondents of the research were 50 nurses of the hospital on intensive care polyclinic selected through census method in sampling. The research data were analyzed by using multiple linear regression analysis method. The result proves that commitment, working motivation, and professionalism simultaneously or partially affected positively and significantly toward the service quality at regional Public Hospital of Undata Palu. Meanwhile, the determination coefficient indicates Adjusted R-Squre was 0,790 showing that 79% the service quality variable influenced by variables of commitment, working motivation, and professionalism whereas the rest was 21% explained by other variable which is not examined in the research.